Revisiting the taxonomy of Abutilon australiense (Malvaceae), a little known species of peninsular India - Nimbalkar, Varsha Vilasrao; Nandikar, Mayur D.; Sardesai, Milind M. (Phytotaxa, 2019)
A widely distributed infraspecific taxon, Abutilon indicum subsp. albescens var. australiense is collected after lapse of six decades from peninsular India and recognized here as distinct species, Abutilon australiense comb. et stat. nov. The detailed comparative morphology with its associated taxa has been discussed in the present article with updated nomenclature and typification.